ANALISIS EFISIENSI PRODUKSI PETANI PADI PESERTA OPERASI PANGAN RIAU MAKMUR (OPRM) DI KABUPATEN ROKAN HULU - Desma Harmaidi; Suardi Tarumun; Rosnita ' (PEKBIS, 2016)
A province of Indonesia which makes the production centers program in maintaining national food availability is Riau Province, it’s because from 2008 - 2012 Riau Province that rice deficit with average almost 248 315 tons annually. So that, to have the needs of regional rice, Riau province is very dependent supply of rice from outside of Riau like West Sumatra. In order to reduce dependence on rice supplies from outside of the region in 2013, so that in 2009 Riau government make a Operation Food Riau Makmur (OPRM) program. The purpose of this research were is to analyze the factors that affect rice production and the level of technical efficiency and farming allocate in Rokan Hulu. The analytical method used is the analysis of qualitative (descriptive) to answer the first goal, the analysis of the Cobb-Douglas production function to answer the second goal and frontier production function and cost dual function of border with DEAP approach to answer the third goal. The results showed that the area of land, urea fertilizer, SP36, manure, labourer, farming experience and education to significantly affect production. Generally the farmers as participants OPRM program and non-participants OPRM program have been technically efficient but not efficient as the manner allocate and economically.